2005
DOI: 10.1080/08910600510028433
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic strains ofLactobacillusandBifidobacteriumaffect the translocation and intestinal load ofEnterobacteriaceaedifferently after D-galactosamine-induced liver injury in rats

Abstract: Department of Surgery, University Hospital Malmö , Lund University, Sweden AbstractIn an acute liver injury model we compared the effects of different Lactobacillus and Bifidobacterium strains on bacterial translocation, intestinal load of Enterobacteriaceae and the extent of liver injury. This was an experimental study carried out in an university hospital in Sweden. Sprague-Dawley rats were divided into six groups: liver injury control and five groups of liver injury with administration of three different La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Most of these bacteria act on TG, TC, HDL, and LDL in the serum, thereby reducing blood lipids. It has also been reported that the content of TG in the serum of patients with hyperlipidemia is significantly negatively correlated with Bifidobacterium and Lactobacillus , and positively correlated with Enterobacteriaceae and Enterococcus ( Osman et al., 2005 ). Our study found that the abundances of Agathobacter and Faecalibacterium in the intestines of elderly patients with hyperlipidemia were positively correlated with serum TG and LDL levels, while Bifidobacterium abundance was negatively correlated with the serum LPa level.…”
Section: Discussionmentioning
confidence: 94%
“…Most of these bacteria act on TG, TC, HDL, and LDL in the serum, thereby reducing blood lipids. It has also been reported that the content of TG in the serum of patients with hyperlipidemia is significantly negatively correlated with Bifidobacterium and Lactobacillus , and positively correlated with Enterobacteriaceae and Enterococcus ( Osman et al., 2005 ). Our study found that the abundances of Agathobacter and Faecalibacterium in the intestines of elderly patients with hyperlipidemia were positively correlated with serum TG and LDL levels, while Bifidobacterium abundance was negatively correlated with the serum LPa level.…”
Section: Discussionmentioning
confidence: 94%
“…LP299v is a gram-positive lactic acid bacterium that was isolated from the mucosa of human intestines and is also commonly found in food products [41]. An important char-acteristic of this strain lies in its ability to adhere to the gut wall by mannose-dependent adhesion, which seems to play a crucial role in decreasing bacterial translocation [42][43][44][45] and preventing the adhesion of different pathogens to the intestinal epithelium [46][47][48]. Moreover, LP299v has been shown to reduce the symptoms of irritable bowel syndrome and gastrointestinal adverse events during antibiotics exposure [49][50][51].…”
Section: Discussionmentioning
confidence: 99%